Dyskinetic syndrome in tarantula spiders (Theraphosidae). Issue 8 (3rd August 2018) - Draper, Emily; Trim, Steven A.
ABSTRACT: There have been increasing reports of cases of erratic movements and ataxia followed by death in tarantula species. This paper covers a brief review of what we know about the condition and what to look for in a tarantula patient. This is the first paper on this syndrome and thus hypotheses on causality and treatment options are in their infancy. The paper concludes with a call for more case reports to be published or sent to the attention of the authors such that we can continue to build on the data we already have to seek a better treatment option.